Treated wastewater irrigation effects on aggregate stability of Sandy loam soils in Semi-arid Tropical Zone of Nigeria. (2022) - A, A; Adamu, Adamu; Hayatu, Hayatu; B.S, B.S; Adam, Adam; A, I.; Aliyu, Aliyu; R.W, R.W; Garba, Garba; M.D, M.D; Aliyu, Aliyu; J, J; et al.
No abstract available